Islamic Education and Archipelago Culture - Saepullah, Aep (Proceedings: International Seminar On Educational Studies, 2025)
Islamic education in the archipelago is the result of a creative dialectic between universal Islamic values and the local cultural reality that is deeply rooted in the traditions of the island communities. It has grown into a system that not only transfers knowledge, but also transforms personalities and instills good manners. In the context of the Islamic civilization of the archipelago, education functions as the primary instrument for shaping the identity and character of the people. Through institutions such as Islamic boarding schools, prayer rooms, madrasas, and meunasah, Islamic values blend with language, art, and customs, giving rise to a friendly and moderate face of Islam. This article examines the reciprocal relationship between Islamic education and the culture of the archipelago through a historical-philosophical approach with qualitative-descriptive analysis. The focus of the study is directed at the role of Islamic educational institutions as agents of culture, the internalization of Aswaja values in the context of plurality, and the relevance of Islamic education in the archipelago in facing the challenges of modernity and globalization. The results of the study show that the Islamic education system in the archipelago not only produces scholars and intellectuals, but also maintains the continuity of Islamic civilization rooted in local wisdom. Amidst the disruption of values, civilized and cultured Islamic education is key to maintaining the spiritual and cultural integrity of the nation.